INTEGRASI ERGONOMIC CHECKPOINTS AND 5S UNTUK PENINGKATAN LINGKUNGAN KERJA PADA UMKM BENGKEL: STUDI KASUS BENGKEL KETOK MAGIC CAK MAD - Muhammad Thoriq Rosyadi; Nailul Izzah; Auditya Purwandini Sutarto (LENVARI, 2026)
Working conditions in small and medium enterprises (SMEs), particularly in automotive workshops, often do not meet ergonomic standards, leading to safety risks and reduced productivity. This study aims to implement an integrated Ergonomic Checkpoints–5S approach to evaluate and improve the working environment at Cak Mad Auto Body Repair Workshop. This study is among the few to integrate Ergonomic Checkpoints and 5S/5R within the context of small and medium-sized automotive workshops, whereas these approaches have previously been applied primarily in large-scale manufacturing industries or other types of SMEs. Data were collected through direct observation, Ergonomic Checkpoints checklist assessment, and measurement of lighting and noise levels using a multifunction environment meter. Out of 132 checklist items, 64 relevant aspects were evaluated, with 39 classified as compliant and 25 requiring improvement. The findings indicate that key issues include inadequate lighting, excessive noise levels, poor machine safety, and disorganized tool layout. The implementation of the Ergonomic Checkpoints–5R integration generated improvement recommendations across five priority aspects, including work tool organization, development of safety SOPs, use of personal protective equipment (PPE), and improvements to lighting systems and work areas. Visually, the post-improvement conditions showed a more organized workspace, better arrangement of tools, and improved safety and comfort within the workshop environment.